ASUHAN KEPERAWATAN PADA LAKI-LAKI DEWASA DENGAN DIAGNOSA Chronic Kidney Desease (CKD) - Mona Ariestia (Akper Kesdam I/Bukit Barisan Padang, 2019)
Chronic Kidney Disease (CKD) is a world health problem that is difficult to cure with an increasing incidence, prevalence and morbidity rate. One of the clinical conditions that occurs due to this disease is lung disease caused by a combination of fluid buildup in the alveoli, which causes gas exchange disorders. The aim of this literature study was to conduct a literature study explored the management of nursing care with CKD in adult males. This research design was prepared using a descriptive method approach. The data method used in this research is the documentation method. The documentation method is a data study method by finding or deleting data from text books, journals, scientific articles, literature reviews that contain careful concepts. The data that have been obtained from various literature are collected as a single document used to answer the problems that have been formulated. The results and discussion are based on data analysis based on data analysis that requires effective communication skills, nursing diagnoses are adjusted to the patient's condition, supported planning with supporting facilities and facilities. Conclusions and suggestions to pay more attention to caring for local health workers should increase the motivation of patients and undergo treatment in care.